Zagadnienie dopuszczalności badania przez organ egzekucyjny. Czy wystawca tytułu wykonawczego posiada status wierzyciela — na przykładzie tytułów wystawionych przez Dolnośląskie Biuro Geodezji i Terenów Rolnych - Tenenbaum-Kulig, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The subject of this article is the analysis of the possibility to examine by administrative enforcement authority if the enforcement title’s issuer is acreditor. The author presents opposite views expressed in literature and jurisprudence which are based on article 29 of the Act on enforcement proceedings in administration. Furthermore, the article provides an example of the case where judgement based on the above was passed by the Court of Appeal in Wrocław on 29 April 2009 and describes the motives of the verdict in both resorts. In aconclusion the author presents aposition that enforcement authority’s examination whether the enforcement title comes from acreditor does not breach aban to evaluate the legitimacy and the maturity of aduty described in the enforcement title.
Keywords: organ egzekucyjny; dopuszczalność badania; wystawca tytułu wykonawczego; wierzyciel; Dolnośląskie Biuro Geodezji i Terenów Rolnych